Transient Changes in Defence Gene Expression and Phytohormone Content Induced by Acibenzolar-S-Methyl in Glasshouse and Orchard Grown Kiwifruit - Reglinski, Tony; Wurms, Kirstin; Vanneste, Joel; Ah Chee, Annette; Yu, Janet; Oldham, Jenny; Cornish, Deirdre; Cooney, Janine; Jensen, Dwayne; Trower, Tania; Taylor, Joseph; Schipper, Magan; et al. (Frontiers in Agronomy, 2022)
Acibenzolar-S-methyl (ASM), the active ingredient in Actigard® (Syngenta), is a plant defence elicitor used for the management of bacterial canker caused by Pseudomonas syringae pv. actinidiae (Psa) in kiwifruit. We examined changes in gene expression and phytohormone content in two kiwifruit cultivars, ‘Hayward’ (Actinidia chinensis var. deliciosa) and ‘Zesy002’ (Actinidia chinensis var. chinensis), following ASM application. In glasshouse studies, ASM-induced resistance to stem inoculation with Psa was accompanied by upregulation of salicylic acid (SA) defence pathway genes (PR1, PR2 and PR5) in stems and leaves. The expression of PR1 in ASM-treated plants increased by c. 5-fold in ‘Hayward’ and by over 15-fold in ‘Zesy002’, relative to the untreated controls, whereas PR2 and PR5 increased by up to 4-fold in both cultivars. Orchard studies over three seasons confirmed the utility of PR1, PR2 and PR5 for monitoring ASM-induced responses in mature vines. PR1 and PR5 were more strongly induced by ASM than PR2 and gene upregulation in ‘Hayward’, was accompanied by a reduction in Psa leaf spotting; no such relationship was measurable for ‘Zesy002’ because leaf spot symptoms are rarely expressed. In the third season, six additional gene candidates, BAD, Gluc2, Class IV Chit, EDS1A, NPR3 and NIMIN2, were responsive to ASM in ‘Hayward’ and ‘Zesy002’. Gene upregulation was transient, with expression levels increasing by 1 d after ASM application and declining to control levels between 7–14 days. Moreover, the amplitude of gene upregulation depended on leaf developmental stage and was greater in the first true leaf and the youngest mature leaves than in immature leaves along the same shoot. Phytohormone content did not show a repeatable response pattern to ASM in potted plants or in vines possibly as a consequence of their wider role in regulating plant growth and mediating environmental responses. In conclusion, this study demonstrates that defence gene expression can be used to monitor responsiveness to ASM in two genetically distinct mature kiwifruit cultivars (‘Hayward’ and ‘Zesy002’) under orchard conditions. The use of defence marker genes could be of broader utility across kiwifruit species and could be used to guide ASM application schedules in the orchard.